Temporal Variation of the Skin Bacterial Community and Batrachochytrium dendrobatidis Infection in the Terrestrial Cryptic Frog Philoria loveridgei - Familiar López, Mariel; Rebollar, Eria A.; Harris, Reid N.; Vredenburg, Vance T.; Hero, Jean-Marc (Frontiers in Microbiology, 2017)
In animals and plants, symbiotic bacteria can play an important role in disease resistance of host and are the focus of much current research. Globally, amphibian population declines and extinctions have occurred due to chytridiomycosis, a skin disease caused by the pathogen Batrachochytrium dendrobatidis (Bd). Currently amphibian skin bacteria are increasingly recognized as important symbiont communities with a relevant role in the defense against pathogens, as some bacteria can inhibit the growth of Batrachochytrium dendrobatidis. This study aims to document the Batrachochytrium dendrobatidis infection status of wild populations of a terrestrial cryptic frog (Philoria loveridgei), and to determine whether infection status is correlated with changes in the skin microbial communities. Skin samples of P. loveridgei were collected along an altitudinal range within the species distribution in subtropical rainforests in southeast Australia. Sampling was conducted in two years during two breeding seasons with the first classified as a “La Niña” year. We used Taqman real-time PCR to determine Batrachochytrium dendrobatidis infection status and 16S amplicon sequencing techniques to describe the skin community structure. We found Batrachochytrium dendrobatidis-positive frogs only in the second sampling year with low infection intensities, and no correlation between Batrachochytrium dendrobatidis infection status and altitude, frog sex or size. Skin bacterial diversity was significantly higher in P. loveridgei frogs sampled in the first year than in the second year. In addition, 7.4 % of the total OTUs were significantly more abundant in the first year compared to the second year. We identified 67 bacterial OTUs with a significant positive correlation between infection intensity and an OTU’s relative abundance. Forty-five percent of these OTUs belonged to the family Enterobacteraceae. Overall, temporal variation was strongly associated with changes in Batrachochytrium dendrobatidis infection status and bacterial community structure of wild populations of P. loveridgei.